PATRIARCHAL OPPRESSION ON WOMEN IN PAKISTAN REFLECTED IN MALALA YOUSEFZAI AND CHRISTINA LAMB’S I AM MALALA - Danu Wahyono (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
The study explores the patriarchal oppression on women reflected in Malala Youefzai and Christina Lamb’s I am Malala. The study aims to identify the forms, the cause, and the impact of the patriarchal oppression on women especially on the Pashtun women of the Swat Valley, Pakistan. The research designed used is a qualitative research. Meanwhile, the approach employed is psychological approach. The study shows that there are some forms of patriarchal oppression on women: cultural dominance, powerlessness, exploitation, violence and marginalization. The women are discriminated and mistreated in many ways. The patriarchal oppression on women is the result of the regime of General Zia’s government and also the rules set by the Taliban group. Pashtun women are marginalized. It is an excuse of keeping the Chasity and dignity that the civilization had changed. Culture and tradition play a role as the cause of patriarchal oppression on the Pashtun women where many families dictate a strong preference of sons over daughters. Meanwhile, there are two impact of patriarchal oppression on Pashtun women, physically and emotionally. Many women become illiterate, have no skills except doing housework and end up depending on men for their survival. They also suffer of excessive fear and anxiety and the worst impact is being killed.